Observing the invisible: updating the "japanese identity" in the Kindo practice - considering the fieldwork - Lourenção, Gil Vicente (Faculdade de Ciências e Letras - Unesp - Araraquara., 2012)
The research problem was at the negotiation of the ‘Japanese identity’ in the spaces made possible by doing body-martial called Kendo [Japanese fencing]. The assumption made concerns the indication of an unconscious system of value ranks in terms of proximity and distance in relation a concept of Japaneseness. The phenotypic characters are contingent when it is closest of native knowledge. The Kendo is a Japaneseness device, a mechanism of production of ‘Japanese’ and ‘mythical speeches, upgraded from a subjective and objective body size. In this paper discuss the accessto this ‘group’ from the concept of “participation” in martial practice, referring to anobjectification of the anthropologist body, taken as an’ research instrument ‘.